2009
DOI: 10.1055/s-0028-1112130
|View full text |Cite
|
Sign up to set email alerts
|

Self Concept, Action Control and ADHD Symptoms under Methylphenidate Treatment in Adults with ADHD

Abstract: Positive changes of self-concept and action control features under methylphenidate treatment in this study may encourage therapists to treat adults with ADHD with stimulants, thus not being at risk to decrease their patients' self-efficacy. In combined pharmacological/psychotherapeutic approaches, self-concept scales could be used to predict treatment outcome, and in order to monitor interactions between ADHD symptom reduction and self concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Also, Canu and Carlson [ 58 ] reported that impulsive and hyperactive or impulsive behavior is less negative for flirting partners: in contrast to inattention , it is perceived more as an interesting personality trait, useful in dating and social relations. However, also an overestimation of symptom severity by people with ADHD themselves cannot be ruled out as explanation for the differences [ 9 , 38 , 39 ]. Robbins [ 59 ], for example, assumed that persistent problems with social and family environment lead to low self-esteem and a negative self-view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Canu and Carlson [ 58 ] reported that impulsive and hyperactive or impulsive behavior is less negative for flirting partners: in contrast to inattention , it is perceived more as an interesting personality trait, useful in dating and social relations. However, also an overestimation of symptom severity by people with ADHD themselves cannot be ruled out as explanation for the differences [ 9 , 38 , 39 ]. Robbins [ 59 ], for example, assumed that persistent problems with social and family environment lead to low self-esteem and a negative self-view.…”
Section: Discussionmentioning
confidence: 99%
“…Some tried to find explanations for the higher symptom self-ratings: one possibility could be an overestimation of the minor executive power limitation found in ADHD [ 31 ]. Another explanation is the low self-esteem of people with ADHD and their negative views of themselves [ 9 , 21 , 38 , 39 ]. Lower symptom self-ratings found in ADHD patients may be explained by a positive illusory bias: an unawareness of their own symptoms and impairments [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wearing seat belts is better predicted by a sense of self-efficacy rather than risk perception (Schwarzer et al, 2007). Adults with ADHD have been shown to have, in general, a lower sense of self-efficacy (Edel et al, 2009; Newark & Stieglitz, 2010; Norwalk, Norvilitis, & MacLean, 2009). Unfortunately we did not measure this variable.…”
Section: Discussionmentioning
confidence: 99%
“…Decline of different measures of emotional dysregulation, oppositional symptoms and disorganization in adults with ADHD have been shown as a result of methylphenidate treatment in several randomized placebo-controlled trials (Reimherr et al 2007;R ö sler et al 2009, 2010bMarchant et al 2011). Also improvement of self concept and action control has been observed under methylphenidate treatment in adults with ADHD (Edel et al 2009). Moreover, positive effects of stimulants on a functional level and measures of quality of life have been reported (Spencer et al 2008).…”
Section: Functional Impairmentsmentioning
confidence: 94%